Interpreting exile and double consciousness in conjunction with V. S. Naipaul's The Mimic Men - Paudel, Pradeep, author; Frank, Katherine, advisor; Ribadeneira, Alegria, committee member; Morales, Juan, committee member (Colorado State University. Libraries, 2010)
Written in multi-genre form, this thesis interweaves the personal and academic writing by negotiating among various forms of genres, such as non-fictional prose narrative, epistolary writing, poetry, interior monologue, short fiction and literary criticism to study exile and double consciousness. The genres employed in the thesis are reflective of the ruptured double consciousness, and they also give expression to different emotional instances caused by the sense of exile, dislocation and alienation. The core philosophy of multi-genre writing is to express what is inexpressible through traditional expository narrative and to engage the readers by using vivid expressionist writing. The personal writing in the thesis offers a personal narrative of exile, and the academic writing studies V.S. Naipaul’s The Mimic Men and provides an analysis of exile and its various ramifications, most particularly, double consciousness. By contextualizing the personal experience with the textual analysis on theoretical ground, the thesis tries to develop a synthetic resolution to the traumatic experience of cultural and geographical dislocation.
Covers not scanned.
Keywords: Exile (Punishment) in literature